2019
DOI: 10.17513/use.37275
|View full text |Cite
|
Sign up to set email alerts
|

Late Phase of Atlantic Period of the Holocene in Southern Primorye (Russian Far East)

Abstract: На основе изучения новых, а также исследованных ранее разрезов голоценовых отложений на континентальной и островной частях южного Приморья восстановлена наиболее полная картина ландшафтноклиматических изменений в позднюю фазу атлантического периода голоцена. 1. 6800-6600 календарных лет назад: время первого относительного похолодания, близкого к современному климату. В растительном покрове преобладают широколиственные леса с преимуществом дуба. Хвойно-широколиственные леса играют небольшую роль в горах. 2. 660… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
0
11
0
Order By: Relevance
“…Forest and mire vegetation composition on the Shufan Plateau have changed over the Holocene, with climate probably the primary driver of many of the changes in both settings, as previous palaeoenvironmental studies in the region have concluded (Korotky et al 1997;Lutaenko et al 2007;Mikishin et al 2008;Anderson et al 2017). The studied proxies show different sensitivities to environmental factors; the record from the lake/mire complex shows higher-frequency and more short-lived variations than does the surrounding forest, and it provides the more detailed signal of environmental change.…”
Section: Holocene Changes On the Shufan Plateaumentioning
confidence: 86%
See 4 more Smart Citations
“…Forest and mire vegetation composition on the Shufan Plateau have changed over the Holocene, with climate probably the primary driver of many of the changes in both settings, as previous palaeoenvironmental studies in the region have concluded (Korotky et al 1997;Lutaenko et al 2007;Mikishin et al 2008;Anderson et al 2017). The studied proxies show different sensitivities to environmental factors; the record from the lake/mire complex shows higher-frequency and more short-lived variations than does the surrounding forest, and it provides the more detailed signal of environmental change.…”
Section: Holocene Changes On the Shufan Plateaumentioning
confidence: 86%
“…Korotky et al (1997) estimate mean annual temperatures at 3 °C above present and annual precipitation on the coast at 65-365 mm above present. Maximum warming coincided with the peak of a marine transgression, when the coastline at the head of the Amur Bay shifted 30-40 km landward from its modern position (Korotky 2002;Mikishin et al 2008). Water temperature in the Peter the Great Gulf was 3-6 °C, and locally 11 °C, which is higher than at present (Lutaenko et al 2007).…”
Section: Holocene Changes On the Shufan Plateaumentioning
confidence: 96%
See 3 more Smart Citations